105 Anti-leucine-rich glioma inactivated 1 (LGI1) encephalitis associated with high grade papillary urothelial carcinoma. (23rd August 2021) - Stabler, Jessica; Williams, David
Abstract : Introduction: LGI1 encephalitis is a rare form of limbic encephalitis, that was first recognised as a primary autoimmune phenomenon, and subsequently described in association with a limited number of malignancies. 1 We report a novel case of LGI-1 encephalitis occurring concurrent to a high-grade papillary urothelial carcinoma. Case Presentation: A previously well 72-year-old male presented to a rural hospital with a first episode generalised tonic-clonic seizure, confusion and progressive behavioural change. He was diagnosed with LGI-1 encephalitis, with positive CSF antibodies, and mesial temporal T2 hyperintensity on MRI brain. There was no response to first line treatment with steroids, intravenous immunoglobulin, and mycophenolate. Malignancy screening revealed a lesion within the upper pole of the left kidney, favoured to represent a transitional cell carcinoma. Biopsy demonstrated a low grade papillary urothelial carcinoma. The patient's encephalopathy continued to worsen over a period of months, despite ongoing immunosuppression. He underwent a left nephrouretectomy, and histology demonstrated a high-grade papillary urothelial carcinoma. Subsequent to this, there was improvement in cognition and behaviour. Psychotropic and immunosuppressive medications were slowly weaned. At 9-month follow-up, the patient has returned close to baseline function, and has been clinically stable off all immunosuppressive treatment. Conclusions: LGI-1 encephalitis has previously been described in association with thymoma, lymphoma, teratoma, and more recently with lung and prostate cancer. 2 3 We believe our case is the first report of association between LGI-1 encephalitis and high grade papillary urothelial carcinoma. References: van Sonderen A, et al . Anti- LGI1 encephalitis. Neurology Oct 2016;87(14):1449–1456. Navalli D, Mutalik NR, Jayalakshmi G. Leucine-rich glioma-inactivated protein 1 antibody-positive limbic encephalitis in a patient with adenocarcinoma of prostate: a case report. Ann Indian Acad Neurol Jan-Mar 2019:22(1):121–122. Virupakshaiah A, Dalakas M, Desai N, Mintzer S, Ratliff J. A report on LGI1 encephalitis in association with squamous cell carcinoma of the lung. Neurology Apr 2019;92 (15 Supp):2.2–028.